2021
DOI: 10.1111/syen.12466
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeny of the subfamilyThiotrichinae(Lepidoptera:Gelechiidae) with a revision of the generic classification based on molecular and morphological analyses

Abstract: Thiotrichinae are a subfamily of Gelechiidae with approximately 180 described species in five genera: Calliprora Meyrick, Macrenches Meyrick, Palumbina Rondani, Polyhymno Chambers and Thiotricha Meyrick. The subfamily was established based on two species in a recent molecular phylogenetic study of Gelechiidae, but the monophyly of each genus and the phylogenetic relationships among the genera have not been tested. To address these questions, we performed the first phylogenetic analyses based on seven molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…S3 ). Finally, P. gossypiella , a member of subfamily Apatetrinae, is the sister taxon to all 4 Gelechiinae species in the phylogeny, supporting the current taxonomic arrangement [ 70 ] (Fig. 1 ).…”
Section: Resultssupporting
confidence: 66%
“…S3 ). Finally, P. gossypiella , a member of subfamily Apatetrinae, is the sister taxon to all 4 Gelechiinae species in the phylogeny, supporting the current taxonomic arrangement [ 70 ] (Fig. 1 ).…”
Section: Resultssupporting
confidence: 66%
“…However, in Pulchrala species (e.g., P. chujaensis (Park, 2016) and P. elaeocarpiella Kyaw, Yagi & Hirowatari, 2019: Kyaw et al 2019 ) and other Thiotrichinae species, the adults do not keep their hindlegs upwards when resting. Lee et al (2021) suggested a close relationship between Palumbina and Tenupalpa , and “the hind-tibia with a posterior spur extending 2/3–3/4 length of tarsomere I” as one of the synapomorphies, while “as long or slightly exceeding half the length of tarsomere I” in other Thiotrichinae genera. The longer spur of the hind-tibia shared in Palumbina and Tenupalpa seems to be correlated with their adult resting posture, keeping their hindlegs upward, but the adaptive significance of this behavior is unclear.…”
Section: Discussionmentioning
confidence: 99%
“… Lee et al (2021) showed that Palumbina , Thiotricha , Tenupalpa , and Pulchrala formed a monophyletic group, but the phylogenetic relationships of this group remain controversial. Some shared traits among this group such as “the number of R veins is four in the forewing venation, the pupal morphology such as a pair of sub-triangular projections on the prothorax, and their biological traits of making a portable case” seems to indicate monophyly of this group.…”
Section: Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“… Thiotrichinae is a moderately small subfamily of Gelechiidae , with about 180 described species in seven genera ( Lee et al 2021 ) and is most diverse in Asia. Since the description of the subfamily in 2013, they have been the subject of several studies (e.g., Lee et al 2018 , 2021 ; Kyaw et al 2019 ; Lee and Hayden 2019 ). Lee et al (2021) presented a phylogeny of the subfamily with a revision of the generic classification based on molecular and morphological analyses.…”
Section: Discussionmentioning
confidence: 99%